The Influence of Digital Transformation on the Competitive Advantage of UMKM (Study of UMKM in Pandeglang District, Pandeglang Regency, Banten) - Ronal Chandra (Jurnal Multidisiplin Sahombu, 2026)
This study aims to examine the effect of digital transformation on the competitive advantage of Micro, Small, and Medium Enterprises (MSMEs) in Pandeglang District, Pandeglang Regency, Banten Province. The research employs a quantitative approach with a correlational method and a cross-sectional design. Data were collected from 100 MSME actors using a structured questionnaire, and the sampling technique applied was proportionate random sampling. The variables analyzed include digital transformation as the independent variable, consisting of business process digitalization, digital platform utilization, digital human resource capability, and information system integration, and competitive advantage as the dependent variable. Data analysis was conducted using multiple linear regression with SPSS. The results indicate that digital transformation has a positive and significant effect on MSME competitive advantage, both partially and simultaneously. Among the dimensions, digital platform utilization is identified as the most dominant factor influencing competitive advantage. The coefficient of determination (R²) value of 0.610 shows that 61% of the variation in competitive advantage can be explained by digital transformation variables. These findings suggest that the adoption of digital technologies plays a strategic role in enhancing MSME competitiveness through improved efficiency, market expansion, and innovation. This study contributes to the literature on business administration by providing empirical evidence from a local context and offers practical implications for policymakers and MSME actors in accelerating digital transformation.